Acremonium sp. sebagai Agen Biokontrol Eceng Gondok (Eichhornia crassipes (Mart.) Solms. Laubach) - Daisy S. Kandowangko; Maxi Lengkong; Frans B. Rondonuwu (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Various strategy control Already implemented For control population water hyacinth in the lake Tondano like control in a way mechanical , physical , chemical And biological but Not yet succeed . In a way experience mold phytopathogenic This has cause incidence disease in D. Tondano more from 50%. The research objectives are as follows: (1) to prove that spots leaf tailed on leaf water hyacinth goiter caused by by Acremonium sp., ( 2 ) determine inoculum threshold Acremonium sp., (3) determines severity of leaf spot disease based on spore concentration , (4) determines severity of leaf spot disease based on the number total , and (5) determine based on interaction between level concentration spores And amount water hyacinth sampling​ goiter based on amount dots Neochetina sp. (0: healthy , 5 – 10, > 10 – 30, > 30) was carried out in D. Tondano . Koch's postulates , sporulation Acremonium sp., preparation concentration spores , and home inoculation​ plastic conducted in the Phytopathology Lab , Faculty of Agriculture Unsrat . Design test For application a number of concentration based on amount dots Neochetina sp. leaves water hyacinth goiter use factorial in design random complete with three test . Factor concentration There is three level (0.1 x 10 5 and 1 x 10 6 And factor amount dots Neochetina sp. has four level (0: healthy , 5 – 10, > 10 – 30, > 30). Results study show that inoculum threshold Acremonium sp. is 1 x 10 5 spores /ml, severity disease spots leaf tailed compared straight with level concentration spores , severity disease spots leaf tailed No compared straight with amount dots , and severity disease spots leaf tailed based on interaction concentration spores And amount dots No compared straight